Facilitators of and Barriers to mHealth Adoption in Older Adults With Heart Failure. Issue 8 (August 2018) - Cajita, Maan Isabella; Hodgson, Nancy A.; Lam, Katherine Wai; Yoo, Sera; Han, Hae-Ra
Abstract : The purpose of this descriptive, exploratory study was to assess the perceptions of older adults with heart failure regarding the use of mobile technology and to identify potential facilitators of and barriers to mHealth adoption. Semistructured interviews were used to collect data. Transcripts were analyzed using qualitative content analysis. The findings indicated that older adults do not base their intention to use mHealth solely on perceived ease of use and perceived usefulness, as outlined in the Technology Acceptance Model. The following themes emerged from the content analysis: facilitators included previous experience with mobile technology, willingness to learn mHealth, ease of use, presence of useful features, adequate training, free equipment, and doctor's recommendation; barriers included lack of knowledge regarding how to use mHealth, decreased sensory perception, lack of need for technology, poorly designed interface, cost of technology, and limited/fixed income. Overall, the findings suggest that older adults are willing to use mobile health technology, albeit with reservations. Future researchers who seek to implement mHealth-based interventions should address person-related, technology-related, and contextual barriers, and simultaneously capitalize on the influence of potential facilitators, such as a physician's recommendation, to promote mHealth adoption.